2016
DOI: 10.1007/s00484-015-1128-1
|View full text |Cite
|
Sign up to set email alerts
|

Flowering phenological changes in relation to climate change in Hungary

Abstract: The importance of long-term plant phenological time series is growing in monitoring of climate change impacts worldwide. To detect trends and assess possible influences of climate in Hungary, we studied flowering phenological records for six species (Convallaria majalis, Taraxacum officinale, Syringa vulgaris, Sambucus nigra, Robinia pseudoacacia, Tilia cordata) based on phenological observations from the Hungarian Meteorological Service recorded between 1952 and 2000. Altogether, four from the six examined pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
44
1
7

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 57 publications
7
44
1
7
Order By: Relevance
“…were shown by Szabó et al (2016) and Walkovszky (1998) among our examined species. In contrary their findings in the neighbourhood country, Hungary, we did not find linear trend in the flowering onset data -probably because our data were recorded during the 19th century when the impacts of human induced climatic changes were not yet as influential as in the late 20 th century.…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations
“…were shown by Szabó et al (2016) and Walkovszky (1998) among our examined species. In contrary their findings in the neighbourhood country, Hungary, we did not find linear trend in the flowering onset data -probably because our data were recorded during the 19th century when the impacts of human induced climatic changes were not yet as influential as in the late 20 th century.…”
Section: Discussionsupporting
confidence: 54%
“…Considering the quantification of the FO -T -NAO impact-system, we have also found that the flowering onset (FO) is primarily influenced by the heat conditions of the preceding period of flowering (Menzel, 2003;Szabó et al, 2016), and the impact of winter NAO was negligible. Based on our findings the majority of plants are affected most strongly by the mean bi-monthly or trimonthly temperatures prior to the date of flowering.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since these blossom festivals are culturally and economically important events, they should be timed around specific phenophases, such as flowering date of cherry or peach trees [10]. In temperate regions, these phenophases are very sensitive to small changes in temperature [11][12][13]. The advancement in flowering dates is estimated as 1 to 12 days for each 1 • C increase in spring temperature [14][15][16].…”
Section: Introductionmentioning
confidence: 99%